1997
DOI: 10.1097/00001756-199705260-00042
|View full text |Cite
|
Sign up to set email alerts
|

Functional heterogeneity of left inferior frontal cortex as revealed by fMRI

Abstract: Using functional magnetic resonance imaging (fMRI), we mapped brain activity in six normal volunteers during two silent verbal fluency tasks, one with a phonemic (letter) cue and one with a semantic (category) cue. In comparison with resting state, both tasks activated the anterior triangular portion of the left inferior frontal gyrus (IFG or F3, for third frontal gyrus) and the left thalamus. There were also areas activated in one task but not in the other: the posterior opercular portion of the left IFG for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
124
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(147 citation statements)
references
References 6 publications
22
124
0
1
Order By: Relevance
“…The presence of stronger left lateralization in letter fluency compared to category fluency in typically developing controls was reported by one group (Billingsley et al, 2004) but not others (Gourovitch et al, 2000;Mummery et al, 1996) (Paulesu et al, 1997). It is possible that previous studies did not find this effect because group results, rather than individual-based analyses of lateralization, were provided.…”
Section: Task-related Differences In Activation: Letter Fluency Vs Cmentioning
confidence: 72%
See 1 more Smart Citation
“…The presence of stronger left lateralization in letter fluency compared to category fluency in typically developing controls was reported by one group (Billingsley et al, 2004) but not others (Gourovitch et al, 2000;Mummery et al, 1996) (Paulesu et al, 1997). It is possible that previous studies did not find this effect because group results, rather than individual-based analyses of lateralization, were provided.…”
Section: Task-related Differences In Activation: Letter Fluency Vs Cmentioning
confidence: 72%
“…The letter fluency task relies on basic word knowledge and initiation of efficient lexical retrieval strategies to name appropriate items whereas the category fluency task depends to a greater extent on overlearned semantic knowledge. Both tasks are mediated by left prefrontal cortex in most typically developing individuals (Abrahams et al, 2003;Fu et al, 2002;Gaillard et al, 2000;Gourovitch et al, 2000;Paulesu et al, 1997;Phelps et al, 1997;Szaflarski et al, 2002). Individuals with ASD show impairments on behavioral measure of the letter fluency task relative to typically developing controls (Rumsey and Hamburger, 1988;Rumsey and Hamburger, 1990;Turner, 1999, but see Minshew et al, 1997 adults with severe dyslexia (Rumsey and Hamburger, 1990) and clinical norms (Kleinhans et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this view, the conceptual handling of numbers was associated with activation of the left inferior frontal gyrus and sulcus, premotor cortex, and inferior parietal lobule 17 . The left inferior prefrontal cortex was likewise found to be more active in letter than in semantic fluency tasks 18 . The left prefrontal sectors activated in our study largely overlap with the inferior prefrontal area of other investigations which implicate the inferior frontal gyri and sulci in the mediation of cognitive switching.…”
Section: Discussionmentioning
confidence: 94%
“…Letter fluency is an executive function task mediated by cortical and subcortical brain structures in healthy individuals. Functional imaging studies of verbal fluency have reported left inferior frontal and dorsolateral prefrontal activation (Abrahams et al, 2003;Fu et al, 2002;Gaillard et al, 2000;Gourovitch et al, 2000;Paulesu et al, 1997;Phelps et al, 1997) and right cerebellar activation (Fu et al, 2002;Hubrich-Ungureanu et al, 2002;Weiss et al, 2003). In addition, lesion studies support the role of the frontal lobes (e.g., Baldo et al, 2001) and cerbellum in executive function tasks (Akshoomoff et al, 1992;Levisohn et al, 2000;Paradiso et al, 1997;Riva and Giorgi, 2000;Schmahmann and Sherman, 1997).…”
Section: Discussionmentioning
confidence: 97%